How Much of a Tailwind Have We Had from the Weaker Krone? - Bjørn Naug; Einar W. Nordbø (Norges Bank, 2019)
It is usual to assume that a weaker currency will stimulate exports and improve the balance of trade. Despite the krone's depreciation in recent years, however, exports have grown little and the non-oil trade deficit has widened. This raises questions about what effects the weaker krone has actually had. We find that exports would probably have been much lower without the depreciation of the krone. Our conclusion, therefore, is that there has been a significant tailwind.
hdl:11250/2600185
Keywords: 330